Cross-Game Learning In Preference Elicitation For An Upcycled Food Product - Nacka, Marina; Andreas Drichoutis; Rodolfo M. Nayga Jr. (My University, 2025)
This study investigates consumer willingness to pay (WTP) for an upcycled food product— hazelnut chips made from bio-waste—elicited via experimental auctions. The research design aims in exploring the effect of storytelling as a branding strategy on WTP and consumer purchasing behavior. The experiment is structured into six treatments, incorporating variations in information provision and auction mechanisms. The findings will contribute to understanding consumer preference elicitation and the effectiveness of branding strategies in promoting sustainability in the food industry. Moreover, we examine whether cross-game learning (Giebe et al., 2024) in homegrown value auctions has the potential to mitigate misbidding behavior.
Keywords: upcycled food products, consumer willingness to pay, experimental auctions, storytelling branding, circular economy.